Desiccation as a suitable alternative to cold-storage of phyllosphere samples for DNA-based microbial community analyses - Emily Smenderovac; Karelle Rheault; Marie-Ange Moisan; Caroline Emilson; Élodie Brazeau; Marie-Josée Morency; Patrick Gagné; Vincent Maire; Erik Emilson; Lisa Venier; Christine Martineau (Scientific Reports)
Abstract The study of microbial communities of the plant phyllosphere in remote locations using DNA-based approaches is limited by the challenges associated with their preservation in the field and during transportation. Freezing is a common DNA preservation strategy, but it may be unsuitable for leaf samples, or inaccessible in some locations. Other methods such as desiccation, ethanol or commercial preservatives are potential alternative DNA preservation methods for ambient temperature storage. In this study, we assessed the efficacy of desiccation (with silica gel packs), and of three preservation solutions (95% ethanol, RNAlater, LifeGuard) for the preservation of epiphytic phyllosphere communities of Populus tremuloides and Picea glauca at ambient indoor temperature (21 °C) for up to three weeks. We assessed effects on DNA concentration and quality and used metabarcoding to detect changes in bacterial and fungal communities between treatments over time. A secondary study was conducted on leaves of Populus grandidentata to further test the ability of the desiccation treatment to resolve differences between sampling sites. Silica gel packs were identified as effective ambient temperature preservative of phyllosphere bacterial and fungal communities. There were some changes in the communities compared to immediate extraction due to this treatment, but these changes did not affect the ability to distinguish tree species and sampling locations. Overall, our study supports the use of silica gel pack short term preservation at ambient temperature for phyllosphere samples intended for DNA-based microbial community analyses.